Rapid identification of escolar (Lepidocybium flavobrunneum) and oilfish (Ruvettus pretiosus) species based on recombinase polymerase amplification. (February 2023) - Xie, Ruibin; Zhang, Juan; Wen, Shuang; Zhao, Ruiming; Wang, Nan; Chen, Ailiang
Abstract: Escolar or oilfish being sold as cod is a worldwide concerning food counterfeiting issue. This study established a simple and rapid real-time recombinase polymerase amplification (RPA) assay for oilfish ( Ruvettus pretiosus ) and escolar ( Lepidocybium flavobrunneum ) detection. The assay uses RPA primers and a probe designed for the intraspecific conserved and interspecific regions in the COI and Cyt b genes, respectively. The RPA assay was completed within 20 min at 37 °C, was specific for either oilfish or escolar species, and showed no cross-reactivity with other cod or salmon fishes. The limit of detection for oilfish and escolar was 9.6 pg/μL and 48 pg/μL, respectively. Samples that were cooked or digested retained a detection sensitivity of 1%. This real-time RPA assay is a simple, rapid, reliable, and sensitive method for oilfish or escolar identification which may help control oilfish or escolar adulteration and ensure consumer health. Graphical abstract: Image 1